The mystery of the Hanging Garden of Babylon : an elusive world wonder traced - Dalley, Stephanie (Oxford University Press, 2013)
"Identifies and locates one of the Ancient World wonders -- New description of a very early garden and the technology behind its water supply -- Identifies the early occurrence of the "Water-raising Screw" -- Links Assyrian texts and sculpture to later classical sources and explains legends surrounding the characters of Semiramis and Nebuchadnezzar -- Reassesses specific sculpture in the British Museum." --Publisher.